THE INFLUENCE OF ISLAMIC PERSONALITY ON CUSTOMER LOYALTY - Busyro, Wahyi; Erwandi, Radi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
Indonesia as a country whose population is predominantly Muslim is expected to be a country that can overshadow the development of Islamic banking. The development of Islamic banking can be seen in the development of Islamic bank assets, but its development is still stagnant with a market share of 6.59%. development is still very far from conventional banks. Islam covers all aspects of human life. Aspects of life range from aqidah, morals, worship and, muamalah. As a Muslims, of course, our behavior in muamalah is also based on the Qur'an and hadith. Customer loyalty is closely related to customer behavior. As Muslims we have a personality that every Muslims should have. The hope is that this Islamic personality will create customer loyalty in Islamic banks. If customer loyalty is achieved, the development of Islamic banks will be more advanced in the future. The study used a population of customers at Indonesian Islamic banks located in Pekanbaru with a sample size of 100 people. This study was analyzed using SPSS to obtain the results that Islamic personality affects customer loyalty. The results of this study are expected to be able to contribute to institutions and the government.